Memahami Tafsir dan Urgensinya - M. Agus Yusron (ZAD Al-Mufassirin, 2022)
In the process of understanding the verses of the Qur'an, there are several terms that are quite familiar among academics besides interpretation, namely ta'wil, tadabbur, and hermeneutics. These terms certainly raise pros and cons among academics, especially since the term (hermeneutics) comes from non-Muslims. So for those who contra (reject hermeneutics), feel less suitable to use it in understanding the Qur'an. In this study, we do not discuss in detail the various terms above, although in the initial discussion they will be explained in general terms. This study will explain about the interpretation in general, the difference with ta'wil, how the concept of interpretation and ta'wil in the Qur'an, along with the requirements of a commentator, and the urgency of an interpretation as a scientific product. This research uses a qualitative type of research with a descriptive approach. In general, this study found that interpretation is broader than ta'wil, both in terms of the object of study and urgency, as well as tadabbur or hermeneutics. The urgency of interpretation occupies the highest position, because interpretation is a tariqah (way) to understand kalamullah, as a guide for human life, both in this world and in the hereafter.